Penggunaan Campur Kode dan Alih Kode dalam Pernyataan Tertulis Resmi Pemerintah Kalimantan Tengah - Natalia, Febrina (Kementerian Sekretariat Negara Republik Indonesia, 2019)
In this globalization and digital era, the development of culture which embraces some aspects such as language, information and lifestyle is unavoidable. One of culture development which has a rapid change is language. Language has a crucial role in our life, even in every aspect, we use language to communicate and deliver our thoughts. We live in a world which consists of diversed cultures and languages, even in one region; we may have more than one local language and foreign language. The development of culture somehow affects the ways of people reacting toward their surroundings, mostly in language both in oral conversation and written text. Considering the impacts of multi languages we have, therefore, this paper focuses on analyzing the use of code-mixing and code-switching in officially written remarks of Central Kalimantan government. Official remarks are ones of the essentials needed in each government which are delivered by government officials. But, due to the development of culture nowadays, the official remarks of Central Kalimantan government consist of many foreign (English) words which were categorized as code-mixing and code-switching. Therefore, this paper analyzed three points: (1) types of code-mixing and code-switching used in the official remarks, (2) reasons of using the code-mixing and code-switching in the officially written remarks viewed from the sociolinguistic aspects, and (3) position of the remarks using the code-mixing and code-switching viewed from the perspective of Indonesian Law (Indonesian Law Number 24 Year 2009, Government Regulation of the Republic of Indonesia Number 57 Year 2014, and Presidential Regulation Number 63 Year 2019). Keywords: code-mixing, code-switching, official remarks